Persepsi Masyarakat Muslim Pada Calon Independen - Putra Indah Harahap; Adi Syaputra Sirait (IAIN Padangsidimpuan, 2022)
The General Election (Pemilu) is actually a democratic contest intended for political party cadres. However, with the existence of Law Number 8 of 2015 Article 39 (b) which allows the existence of individual (independent) candidates who do not come from parties but receive full support and stretcher from the community to take part in the General Election. The phenomenon of individual (independent) candidates that occurred in the 2018 Mayoral Election in Padangsidimpuan City is a new phenomenon. Then, the winner was precisely the individual candidate (independent) beating the other two candidates from political parties. So, this study was conducted to determine the extent of the perception of the Muslim community of Padangsidimpuan City regarding individual (independent) candidates in the 2018 Padangsidimpuan Mayoral Election. This research is qualitative with a case study method using a descriptive approach. The research subject is the Muslim community of Padangsidimpuan City with data collection techniques using interviews. Data processing techniques with data reduction, data presentation, and drawing conclusions. The results of this study are the perception of the Muslim community regarding individual (independent) candidates in the 2018 Padangsidimpuan Mayoral Election that individual (independent) candidates have good personality and organizational experience, come from the community or non-political parties and are considered capable of accommodating the aspirations of the community so that will give birth to a better and more advanced Padangsidimpuan City. The reason the Muslim community supports individual (independent) candidates in the 2018 Padangsidimpuan Mayoral Election is the courage to choose an individual (independent) path even though the potential for winning is very small, a good political track record so that they will be more objective in running the government, and have good characteristics and charismatic as a leader.